Exploring the dynamics of hamstring strength in volleyball: A positional perspective through a cross-sectional lens - Soylu, Ç.; Altundag, E. (Turkish Journal of Sport and Exercise, 2024)
To the best of our knowledge, there is no study in the literature examining the isolated eccentric hamstring strength according to the playing positions of volleyball players, but there are few studies evaluating the hamstring muscle strength according to the playing positions. The aim of this study was to compare the eccentric hamstring muscle strength levels of elite volleyball players according to their playing positions. Elite volleyball players (n=31 female and n=32 male) aged between 18-35 who took part in the 2022-2023 Turkish Volleyball 1st League season and were included in a similar training program participated in the study voluntary. Sixty-three volleyball players were categorized as libero (n=5 female and n=6 male), middle player (n=8 female and n=8 male), opposite (n=4 female and n=6 male), setter (n=6 female and n=4 male) and spiker (n=7 female and n=9 male). Eccentric hamstring muscle strength was assessed during Nordic Hamstring exercise (NHE) using IVMES H-Bord (IVMES, Ankara, Turkey) device. As a result of the comparison of the eccentric hamstring strength of the volleyball players according to the positions, it was determined that there was no statistically significant difference between the maximum and mean eccentric hamstring muscle strengths and muscle strength differences of both female (F=0.403-5.331; p=0.255-0.982) and male (F=4.167-6.985; p=0.137-0.384) athletes. In addition, there was no significant difference between male and female athletes in terms of mean and maximum eccentric hamstring muscle strength and muscle strength differences according to their positions (F=0.001-3.823; p=0.055-0.972). In our study, it was found that the eccentric hamstring strength and bilateral strength difference percentages of both male and female volleyball players did not differ according to their positions. The fact that the eccentric hamstring strength levels of volleyball players did not differ according to the positions in previous studies and in our study is thought to be related to the changing structure of volleyball.